2023
DOI: 10.46328/ijonse.103
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Contextualized Digital Game-Based Learning Resource in Improving Kindergarten Pupil’s Alphabet Knowledge Level

Abstract: The achievement of pupils in their future studies depends on their reading skills. One of the strongest foundations in reading success includes alphabet knowledge. Nowadays, the utilization of information communication technology (ICT) influences young children’s learning and emergent literacy skills. Hence, this study explored the effectiveness of digital game-based learning resource in improving pupils’ alphabet knowledge specifically on vowels. An alphabet knowledge checklist on vowels was used to collect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Evaluations of digital games have also shown the games' positive effects on children's development of foundational skills identified by the National Reading Panel (2000) as essential skills for later literacy development. Digital games can promote children's alphabet knowledge (Cornito, 2023), phonemic awareness (Jamshidifarsani et al, 2018), phonics (Savage et al, 2013), vocabulary (Dore et al, 2019), fluency (Giacomo Dina et al, 2016), as well as comprehension (Castro & Sevillano, 2022). Additionally, in a meta-analysis of educational apps with high-quality activities grounded in research-based principles, aimed at improving literacy and math outcomes among children in preschool through third grade, Kim and his colleagues (2021) showed that the magnitude of the impact of these programs are similar to the effect of tutoring interventions (ES = 0.37) and early elementary literacy interventions (ES = 0.39).…”
Section: Game-based Learning In Early Literacymentioning
confidence: 99%
“…Evaluations of digital games have also shown the games' positive effects on children's development of foundational skills identified by the National Reading Panel (2000) as essential skills for later literacy development. Digital games can promote children's alphabet knowledge (Cornito, 2023), phonemic awareness (Jamshidifarsani et al, 2018), phonics (Savage et al, 2013), vocabulary (Dore et al, 2019), fluency (Giacomo Dina et al, 2016), as well as comprehension (Castro & Sevillano, 2022). Additionally, in a meta-analysis of educational apps with high-quality activities grounded in research-based principles, aimed at improving literacy and math outcomes among children in preschool through third grade, Kim and his colleagues (2021) showed that the magnitude of the impact of these programs are similar to the effect of tutoring interventions (ES = 0.37) and early elementary literacy interventions (ES = 0.39).…”
Section: Game-based Learning In Early Literacymentioning
confidence: 99%